Association of HIV infection with clinical features and outcomes of patients with aortic aneurysms. (December 2022) - Chehab, Omar; Kanj, Amjad; Zeitoun, Ralph; Mir, Tanveer; Shafi, Irfan; Pahuja, Mohit; Briasoulis, Alexandros; Doria de Vasconcellos, Henrique; Minhas, Anum; Varadarajan, Vinithra; Wu, Colin; Arbab-Zadeh, Armin; et al.
Data on the characteristics and outcomes of hospitalized patients with aortic aneurysms (AA) and HIV remain scarce. This is a cohort study of hospitalized adult patients with a diagnosis of AA from 2013 to 2019 using the US National Inpatient Readmission Database. Patients with a diagnosis of HIV were identified. Our outcomes included trends in hospitalizations and comparison of clinical characteristics, complications, and mortality in patients with AA and HIV compared to those without HIV. Among 1, 905, 837 hospitalized patients with AA, 4416 (0.23%) were living with HIV. There was an overall age-adjusted increase in the rate of HIV among patients hospitalized with AA over the years (14–29 per 10, 000 person-years; age-adjusted p -trend < 0.001). Patients with AA and HIV were younger than those without HIV (median age: 60 vs 76 years, p < 0.001) and were less likely to have a history of smoking, hypertension, dyslipidemia, diabetes mellitus, and obesity. Thoracic aortic aneurysms were more prevalent in those with HIV (37.5% vs 26.7%, p < 0.001). On multivariable logistic regression, HIV was not associated with increased risk of aortic rupture (OR: 0.79; 95% CI: 0.61–1.01, p = 0.06), acute aortic dissection (OR: 0.73; 95% CI: 0.51–1.06, p = 0.3), readmissions (OR: 1.04; 95% CI: 0.95–1.13, p = 0.4), or aortic repair (OR: 0.89; 95% CI: 0.79–1.00, p = 0.05). Hospitalized patients with AA and HIV had a lower crude mortality rate compared to those without HIV (OR: 0.75 (0.63–0.91), p = 0.003). Hospitalized patients with AA and HIV likely constitute a distinct group of patients with AA; they are younger, have fewer traditional cardiovascular risk factors, and a higher rate of thoracic aorta involvement. Differences in clinical features may account for the lower mortality rate observed in patients with AA and HIV compared to those without HIV.